1973
DOI: 10.1177/0310057x7300100507
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Dreaming during Anaesthesia in a Paediatric Hospital

Abstract: Su:\IMARY ~lost studies of awareness and dreaming during general anaesthesia exclude children because of uncertainty of accurate communication, but the authors consider that, with care and patience, children over about 7 years of age can give sensible and useful information. A prospective study was carried out in which 202 patients aged between 7 and 1-1 years undergoing general anaesthesia for a wide range of surgical procedures were interviewed post-operatively, and a questionnaire was sent to the parents ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1
3

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 5 publications
(3 reference statements)
2
23
1
3
Order By: Relevance
“…Few previous studies have examined awareness in children. In 1973, an audit of 202 children aged 7-14 years found an incidence of 5% (7). Many of the children in that study who reported awareness had an anesthetic without a volatile drug.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few previous studies have examined awareness in children. In 1973, an audit of 202 children aged 7-14 years found an incidence of 5% (7). Many of the children in that study who reported awareness had an anesthetic without a volatile drug.…”
Section: Discussionmentioning
confidence: 98%
“…One study, performed in 1973, found an incidence of awareness in children of 5% (7). In this study, some children received nitrous oxide, a neuromuscular blocker, and no volatile or continuous IV anesthetic-the Liverpool technique.…”
mentioning
confidence: 89%
“…In einer älteren Arbeit wurde eine Inzidenz intraoperativer Wachheit bei 7-bis 14-jährigen Kindern von bis zu 5 gefunden. Hier kamen allerdings Anästhe-sieverfahren zur Anwendung, die heute nicht mehr zum Standard zählen [11].…”
Section: Diskussionunclassified
“…Zwar liegt die Inzidenz von Episoden intraoperativer Wachheit bei Erwachsenen im Promillebereich, dennoch fürchten Patienten gerade diesen Zwischenfall mit am häufigsten [20]. Es gibt deutliche Hinweise darauf, dass diese Inzidenz bei Kindern mindestens ebenso hoch, wenn nicht sogar um ein Vielfaches höher ist als bei Erwachsenen [3,4,8,11,16]. Daher erscheint ein objektivierbares Monitoringverfahren gerade in der pädiatrischen Anästhesie wünschens-wert.…”
unclassified
“…Wachheit in Narkose wird bei Erwachsenen mit einer Inzidenz von 0,1-0,2% angegeben [66,103].Bei Kindern liegen älte-re Berichte vor, nach denen Wachheit mit einer Frequenz von 5% bei 7-bis 14-Jäh-rigen beobachtet wurde [76].Spätere Untersuchungen haben das allerdings nicht bestätigen können [44,85]. Der Verzicht auf volatile Anästhetika erhöht bei Erwachsenen das Risiko intraoperativer Wachheit [29].Es ist vollkommen unklar, ob das auch bei Kindern zutrifft.…”
Section: Wachheit In Narkoseunclassified